2022
DOI: 10.1002/aoc.6920
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of proton conduction between two new Cd(II) and Co(II) complexes and in vitro antibacterial study of the Cd(II) complex

Abstract: Two new complexes based on 4,4′‐[1,3‐phenylenebis(oxy)]diphthalic acid (H4L) ligands were synthesized, namely, [Cd2(L)(1,10‐phen)2(H2O)]n(1) and [Co2(L)(1,10‐phen)2(H2O)]n(2), in which 2D structures transform into 3D supramolecular structures by CH···π interaction. The proton conductivity of complexes 1 and 2 at low temperature is close (σ1 = 3.12 × 10−8 S cm−1 and σ2 = 3.81 × 10−8 S cm−1 at 30°C), but these two complexes show different conduction mechanisms. The Vehicular mechanism in 1 is caused by the O···… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The arc radius of the Nyquist circle reflected the charge transfer resistance. Smaller charge transfer resistance might be conducive to the separation and transfer efficiency of the optical carrier [ 32 , 33 ]. The ohmic resistance (R S ) and the charge transfer resistance (R CT ) of BGA-4 were 39.73 Ω and 54.15 Ω, substantially lower than those of GA (42.26 Ω and 111.74 Ω), which indicated that BiOCl could improve the conductivity and electron transfer capacity of BGA-4 composite.…”
Section: Resultsmentioning
confidence: 99%
“…The arc radius of the Nyquist circle reflected the charge transfer resistance. Smaller charge transfer resistance might be conducive to the separation and transfer efficiency of the optical carrier [ 32 , 33 ]. The ohmic resistance (R S ) and the charge transfer resistance (R CT ) of BGA-4 were 39.73 Ω and 54.15 Ω, substantially lower than those of GA (42.26 Ω and 111.74 Ω), which indicated that BiOCl could improve the conductivity and electron transfer capacity of BGA-4 composite.…”
Section: Resultsmentioning
confidence: 99%
“…Coordination polymers (CPs) assembled with metal ions/clusters and organic ligands are a class of crystalline complexes and have attracted great attention in sensing detection, separation, and adsorption due to their designable and tunable structures and functional porosity. Recently, CPs have become a new candidate material for proton conduction as the hydrogen-bond networks could be formed through introducing typical ligands with hydrophilic units or proton carriers. In this way, high-conductivity CPs are constructed with good proton transport paths. Most importantly, the visualization of the structure of CPs provides an opportunity to explore the proton conduction mechanism and pathway, which makes it possible to analyze the structure–property relationship in depth.…”
Section: Introductionmentioning
confidence: 99%
“…These materials have demonstrated excellent potential employment in multiple aspects, for example, sensing [ 18 , 19 , 20 , 21 , 22 ], photocatalysis [ 23 , 24 , 25 ], heterogeneous catalysis [ 26 , 27 , 28 , 29 ], gas storage [ 30 , 31 , 32 , 33 ], and drug delivery [ 34 , 35 , 36 ]. They are well known for their extensive structural tunability, high porosity, unique physicochemical properties, and light reactivity.…”
Section: Introductionmentioning
confidence: 99%